Studi Fenomenologi : Coping Mechanism dalam Menghadapi Bencana Banjir di Kelurahan Kec. Singkil - Astrid L. Mandas; Delovina Mende; Yossy Korengkeng (Journal Of Psychology humanlight, 2025)
This study aims to explore the coping mechanisms developed by the residents of Karame Village, Singkil District, in facing recurring flood disasters. Using a qualitative phenomenological approach, the research reveals that the community has internalized both problem-focused and emotion-focused coping strategies as part of their everyday lives. The findings show that floods are no longer perceived as traumatic events but as predictable occurrences that the community is emotionally and practically prepared to handle. Adaptive responses include the construction of multi-story houses, reliance on early warning information, strong social solidarity, and emotional support within families and neighborhoods. Cultural values such as gotong royong (mutual cooperation) play a key role in accelerating recovery and fostering psychological resilience. The study highlights the importance of integrating psychosocial and community-based approaches in disaster mitigation programs, emphasizing the lived experiences and collective strength of local communities.